2017
DOI: 10.1182/bloodadvances.2017008060
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput sequencing reveals novel features of immunoglobulin gene rearrangements in Burkitt lymphoma

Abstract: We thank Ralf Küppers for his interest in our article 1 and for his thoughtful commentary. 2 We address each of the points he raises below. First, Küppers claims that, in contrast to what has been demonstrated in mice,3 not all normal human B-cell progenitors undergo concurrent biallelic D H J H rearrangement during B-cell development, and he cites an analysis performed with Southern blot techniques of 26 B-cell lines derived from 3 individuals to support this claim. 4 We analyzed publicly available IGH high-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Another study showed that while the leukemic clone could be identified in both DNA and RNA, the transcriptional clonal frequencies were generally lower [56]. Caution is warranted because not all rearrangements are transcribed, as shown by several studies [57][58][59]. As RNA-sequencing has often been performed using shorter reads in its more general application, the robustness becomes apparent from the results presented by Blachly et.…”
Section: Type Of Materials Used In Mrd Measurementsmentioning
confidence: 99%
“…Another study showed that while the leukemic clone could be identified in both DNA and RNA, the transcriptional clonal frequencies were generally lower [56]. Caution is warranted because not all rearrangements are transcribed, as shown by several studies [57][58][59]. As RNA-sequencing has often been performed using shorter reads in its more general application, the robustness becomes apparent from the results presented by Blachly et.…”
Section: Type Of Materials Used In Mrd Measurementsmentioning
confidence: 99%